Energetic but insensitive spiro‐tetrahydrotetrazines based on oxetane‐3‐one. (6th June 2022) - Fessard, Thomas C.; Gospodinov, Ivan; Klapötke, Thomas M.; Stierstorfer, Jörg; Voggenreiter, Michael
Abstract: Energetic oxetanes were first described in the 1970s, such as 3, 3‐bis(azidomethyl)oxetanes (BAMO) and 3‐(nitratomethyl)‐3‐(methyl)oxetanes (NIMMO). Over the past few years, oxetanes were hardly available only as special‐purpose chemicals for the pharmaceutical industry. Oxetan‐3‐one is condensed with energetic compounds with a hydrazino function such as amino‐nitroguanidine and picryl hydrazine to form energetic Schiff bases. Hydrazinolysis of the guanidine derivatives lead to energetic spiro ‐tetrahydrotetrazines which are quite rare in literature. All products were characterized by their crystal structure using single‐crystal X‐ray diffraction. Furthermore, the new compounds were analyzed using IR, EA, DTA, and multinuclear NMR spectroscopy ( 1 H and 13 C). The sensitivities towards external stimuli such as friction and impact were determined according to BAM standards and the energetic performances were calculated using the EXPLO5 code. Abstract : Carbonyl functions such as ketones and aldehydes are extremely versatile chemical groups. Oxetan‐3‐one is functionalized via condensation with energetic compounds having a hydrazino function to form Schiff bases. Further functionalization with hydrazine lead to several unexpected but energetic spiro ‐tetrahydrotetrazines which were characterized by their X‐ray structure.